Medicinal Uses, Biological and Chemical Properties of Wild Plum (Harpephyllum caffrum): An Indigenous Fruit Plant of Southern Africa - Alfred Maroyi, (Journal of Pharmacy and Nutrition Sciences, 2019)
Harpephyllum caffrum is a fruit plant widely used as herbal medicine throughout its distributional range in southern Africa. This study was aimed at providing a critical review of the biological activities, phytochemistry and medicinal uses of H. caffrum. Documented information on the botany, biological activities, medicinal uses and phytochemistry of H. caffrum was collected from several online sources which included BMC, Scopus, SciFinder, Google Scholar, Science Direct, Elsevier, Pubmed and Web of Science. Additional information on H. caffrum was gathered from pre-electronic sources such as book chapters, books, journal articles and scientific publications sourced from the University library. This study showed that the bark, fruits and roots of H. caffrum are used as blood purifier and emetic, and as herbal medicine against asthma, wounds, bone fractures, sprains and skin problems. Phytochemical compounds identified from the fruits, leaves and stem bark of H. caffrum include cardanols, fatty acid esters, flavonoids, phenolics and triterpenoids. Ethnopharmacological research revealed that H. caffrum extracts and compounds have in vitro and in vivo pharmacological activities such as acetylcholinesterase, analgesic, antibacterial, anticonvulsant, antimycobacterial, antifungal, anti-HIV, anti-inflammatory, antioxidant, antipyretic, melanogenesis and antityrosinase, hypoglycaemic and hypotensive, hepatoprotective and cytotoxicity activities. Harpephyllum caffrum should be subjected to detailed phytochemical, pharmacological and toxicological evaluations aimed at correlating its medicinal uses with its phytochemistry and pharmacological activities of the species.